2005
DOI: 10.1007/s10549-005-4615-y
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Local and Distant Disease Relapse in Patients with Breast Cancer Treated with Primary Chemotherapy: Do Patients with a Complete Pathological Response Differ from Those with Residual Tumour in the Breast?

Abstract: This study aimed to evaluate patterns of local and distant disease recurrence in patients having primary chemotherapy and compared patterns of relapse in patients with a complete pathological response with those who had residual breast disease. This is an observational study using a sequential series of patients treated with primary chemotherapy. They were followed up for a minimum of 5 years. All data was collected prospectively. Three hundred forty-one consecutive patients with breast cancer were treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 28 publications
(68 reference statements)
0
24
0
Order By: Relevance
“…The excellent long-term local and distant control achieved in this patient allow us to maintain hope for women to preserve their breast even with locally advanced disease. Several authors have reported unacceptably high local-regional and ipsilateral breast tumor recurrence rates and poorer OS in LABC patients, not primarily eligible for conservative treatment, who underwent BCT after primary chemotherapy (LRR rate up to 28%) [12, 13], suggesting some differences between de novo BCT and BCT following primary chemotherapy.In contrast to these reports, other studies reported satisfactory local (≀5%) and distant control in LABC downstaged with primary chemotherapy [12, 14, 15], by adopting careful patient selection, as for patients with early breast cancer treated by breast conservation without initial primary chemotherapy. In our study, overall BCT patients had a clinical response >50%, residual tumor size ≀3 cm as a solitary lesion, negative resection margins and resolution of skin and/or chest wall involvement and radiation.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The excellent long-term local and distant control achieved in this patient allow us to maintain hope for women to preserve their breast even with locally advanced disease. Several authors have reported unacceptably high local-regional and ipsilateral breast tumor recurrence rates and poorer OS in LABC patients, not primarily eligible for conservative treatment, who underwent BCT after primary chemotherapy (LRR rate up to 28%) [12, 13], suggesting some differences between de novo BCT and BCT following primary chemotherapy.In contrast to these reports, other studies reported satisfactory local (≀5%) and distant control in LABC downstaged with primary chemotherapy [12, 14, 15], by adopting careful patient selection, as for patients with early breast cancer treated by breast conservation without initial primary chemotherapy. In our study, overall BCT patients had a clinical response >50%, residual tumor size ≀3 cm as a solitary lesion, negative resection margins and resolution of skin and/or chest wall involvement and radiation.…”
Section: Discussionmentioning
confidence: 77%
“…breast-conserving therapy (BCT), remains a great challenge for both oncologists and surgeons [9,10,11,12] because of concerns about unacceptably high local failure rates reported by several studies [12, 13]. In contrast to these reports, other studies reported satisfactory local and distant control in LABC downstaged with primary chemotherapy [12, 14, 15]. In summary, local-regional relapse (LRR) rates ranged from 1 to 28% [12], but most studies included small numbers of patients with T4 disease, together with other LABC, such as T2 and T3 or any T-N 2–3 , thus making interpretation of the data difficult.…”
Section: Introductionmentioning
confidence: 99%
“…The emerging standard treatment for LABC involves multimodality treatment with neoadjuvant chemotherapy. Although there is no evidence to suggest that there is a survival benefit of neoadjuvant chemotherapy when compared with adjuvant treatment, some studies have shown an overall survival benefit for those patients who achieve a pathologic complete response after neoadjuvant chemotherapy compared with patients without a complete response (6)(7)(8)(9)(10)(11). An advantage of neoadjuvant chemotherapy is that it decreases tumor bulk and may allow breast-conserving therapy.…”
mentioning
confidence: 99%
“…2 There was a statistically significant correlation between pathologically complete response and both overall survival and disease-free survival. [4][5][6][7][8] Therefore, for patients who are receiving NAC, pCR is the most relevant prognostic factor.…”
mentioning
confidence: 99%